HUKUM, EKONOMI DAN KESEJAHTERAAN: Telaah Yuridis atas Dinamika Pengaturan dan Implementasi Pasal 33 UUD 1945 - Udiyo Basuki (Al-Mazaahib)
The emergence of a school economic in the world will always be associated with the school of economic that have developed previously, so is the pattern of the Indonesian economy. Fierce struggle of capitalism and socialism gives a significant influence toward Indonesian economic ideology. Pancasila as the foundation of economic nation, through the dialectical process raises three kinds of terms that is the constitution of the economy, the economic constitution, and economic Pancasila, the three have the same phrase with a different meaning. The idea of democracy in economy are listed in UUD 1945 Article 33 paragraph (4) does contain the idea of political democracy as well as economic democracy. That is, the highest authority of the State of Indonesia is the people, both in the field of politics or the economy. Indonesia which has more give priority to economic growth from economic equality appears to have difficult times, the economic crisis experienced since mid-2007 has been a fundamental component of economic meluluhlantahkan until economic growth rate for 2008 was measured with a minus sign. This condition indicates that since the signing of the 21st century, Indonesia is not ready to face the era of free trade.